Specific Chemical and Genetic Markers Revealed a Thousands-Year Presence of Toxic Nodularia spumigena in the Baltic Sea - Cegłowska, Marta (Mar Drugs, 2018)
In the Baltic Sea, diazotrophic cyanobacteria have been present for thousands of years, over the whole brackish water phase of the ecosystem. However, our knowledge about the species composition of the cyanobacterial community is limited to the last several decades. In the current study, the presence of species-specific chemical and genetic markers in deep sediments were analyzed to increase the existing knowledge on the history of toxic Nodularia spumigena blooms in the Baltic Sea. As chemical markers, three cyclic nonribosomal peptides were applied: the hepatotoxic nodularin, which in the sea was detected solely in N. spumigena, and two anabaenopeptins (AP827 and AP883a) characteristic of two different chemotypes of this species. From the same sediment samples, DNA was isolated and the gene involved in biosynthesis of nodularin, as well as the phycocyanin intergenic spacer region (PC-IGS), were amplified. The results of chemical and genetic analyses proved for the first time the thousands-year presence of toxic N. spumigena in the Baltic Sea. They also indicated that through all this time, the same two sub-populations of the species co-existed.